Kemajuan Sistem Penghantaran Obat Sublingual: Formulasi, Karakteristik, Farmakokinetik, dan Aplikasi Klinis - Shelsabila Dhea Liffany; Ba’dhiva Yusviar Novia; Nafrila Raheny Sulistyowati; Elisyah Alya Azarina; Silvi Indi Ningsih; Dewi Rahmawati (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Sublingual drug delivery systems have attracted significant attention in modern pharmaceutical technology due to their ability to provide rapid therapeutic effects and bypass first-pass metabolism in the liver. This review article aims to synthesize the relevance of several recent studies on the development of sublingual tablets, including formulation aspects, physicochemical properties, pharmacokinetic parameters, and clinical safety evaluation. Based on literature analysis of various original articles, sublingual tablets have proven to be highly effective for the management of acute conditions such as severe pain (using Sufentanil), angina pectoris (using Nitroglycerin), and motion sickness (using Promethazine HCl), as well as optimal for nutritional supplementation (Cyanocobalamin) and allergy immunotherapy in pediatric populations. The integration of modern excipient technologies, including the use of superdisintegrants and mucoadhesive polymers, plays a crucial role in determining the dissolution profile, systemic bioavailability, and patient comfort. Overall, this article provides an integrative view on how optimization of direct-freezing sublingual formulations contributes to safe and efficient clinical therapeutic success.